Sustainable city concept based on green hydrogen energy - Dincer, Ibrahim; Javani, Nader; Karayel, Kubilay (ELSEVIER, 2022)
The current study investigates the green hydrogen production from renewable energy sources for the metropolitan city of Istanbul by using electrolysers. The main idea is to create a hydrogen map for every district in Istanbul, based on renewable energy sources and water splitting technology. The potentially available renewable sources, such as solar (including offshore), wind (including offshore), biomass, geothermal and underwater current are used for calculating the total hydrogen production potential. Istanbul's potential for producing green hydrogen is estimated to be 7.96 Mt. The study results show that Catalca, S,ile, Silivri, Arnavutko & BULL;y, and Beykoz come out as the districts with the highest green hydrogen potential with 1.49 Mt, 1.19 Mt, 1.12 Mt, 0.57 Mt, and 0.46 Mt, respectively. After supplying the necessary power demand for the city, the remaining power is used to produce green hydrogen which may contribute an economic value of over US $100 billion with a current price of $13/kg of hydrogen and 23.88 billion US$ with a targeted price of $3/kg of hydrogen, respectively. The available potentials for each district are also specifically studied and discussed. It is more importantly expected to reduce the greenhouse gas emissions by about 90% which will ve very important to achieve a carbon-neutral city and hence country due its dominated role. Furthermore, the results provide a clear guidance to enable policymakers and private sectors to use renewable energy potentials for their investment purposes or promote clean energy programs, tackling carbon-based energy consumption, pollution, and greenhouse effect. This, later on, can be used by policymakers and energy providers to help the city and local communities for achieving the United Nation's sustainable development goals.
Keywords: Biomass; Geothermal; Green hydrogen; Society; Solar energy; Sustainable city; Wind energy; Istanbul; FUEL-CELL; ELECTRICITY; CONVERSION; CITIES; Construction & Building Technology; Science & Technology - Other Topics; Energy & Fuels